if x+y+z=0 then find (y-z-x)^3/2 +(z-x-y)^3/2 +(y-z-x)^3/2
Answers
Answered by
3
= (y-z-x)^3/2 + (z-x-y)^3/2 + (y-z-x)^3/2
= y^3/2 - z^3/2 - x^3/2 + z^3/2 - x^3/2 - y^3/2 + y^3/2 - z^3/2 - x^3/2
= ( +y -y +y)^3/2 + ( -z +z -z)^3/2 + ( -x -x -x )^3/2
= y^3/2 - z^3/2 - 3x^3/2
hope this helps you
plz mark as brainiest !!!!
= y^3/2 - z^3/2 - x^3/2 + z^3/2 - x^3/2 - y^3/2 + y^3/2 - z^3/2 - x^3/2
= ( +y -y +y)^3/2 + ( -z +z -z)^3/2 + ( -x -x -x )^3/2
= y^3/2 - z^3/2 - 3x^3/2
hope this helps you
plz mark as brainiest !!!!
Similar questions
Chemistry,
9 months ago
World Languages,
9 months ago
English,
9 months ago
Math,
1 year ago
English,
1 year ago